Transspinal stimulation preceding assisted step training reorganizes neuronal excitability and function of inhibitory networks in spinal cord injury: a randomized controlled trial - Sayed Ahmad, Abdullah M.; Zaaya, Morad; Harel, Noam Y.; Knikou, Maria (Frontiers in Neurology, 2025)
IntroductionIn this pilot randomized sham-controlled clinical trial, we characterized the spinal neuronal and network excitability in human spinal cord injury (SCI) when transspinal stimulation preceded locomotor training within the same session.MethodsFourteen participants with chronic SCI received an average of 40 sessions with 30 Hz transspinal stimulation delivered for 30 min during standing (active: n = 4; sham: n = 5) or supine (active: n = 5) followed by 30-min of robotic assisted step training. Before and 1–2 days after completion of all training sessions, we assessed the soleus H-reflex homosynaptic depression and soleus H-reflex recruitment curve, and the amount of reciprocal and presynaptic inhibition following conditioning stimulation of the antagonistic common peroneal nerve.ResultsTransspinal stimulation administered before locomotor training increased the amount of homosynaptic depression in the active-standing and active-supine groups, while presynaptic inhibition exerted on Ia afferent terminals increased in all study groups. Reciprocal Ia inhibition improved in the sham-standing and active-supine groups while in all groups the excitability threshold of soleus motoneurons decreased.ConclusionThis study demonstrated that transspinal stimulation preceding locomotor training partially restores some of the spinal inhibitory mechanisms acting presynaptic or postsynaptic, and produces network reorganization in chronic SCI. Noninvasive transspinal stimulation can increase the benefits of locomotor training, bringing spinal neuronal networks to a more functional state in chronic SCI.